2003
DOI: 10.1103/physrevlett.90.017201
|View full text |Cite
|
Sign up to set email alerts
|

Phase Coherent Precessional Magnetization Reversal in Microscopic Spin Valve Elements

Abstract: We study the precessional switching of the magnetization in microscopic spin valve cells induced by ultra short in-plane hard axis magnetic field pulses. Stable and highly efficient switching is monitored following pulses as short as 140 ps with energies down to 15 pJ.Multiple application of identical pulses reversibly toggles the cell's magnetization between the two easy directions. Variations of pulse duration and amplitude reveal alternating regimes of switching and non-switching corresponding to transition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
121
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(130 citation statements)
references
References 20 publications
5
121
0
4
Order By: Relevance
“…The present strategy should be compared with those of the SW and the precessional pico-second magnetization reversal. 11,12 As illustrated in Figs. 2͑b͒ and 2͑c͒, the SW strategy is to apply a large enough field to destroy the minimum initial state so that the particle can end up in the target state ͓Fig.…”
Section: Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The present strategy should be compared with those of the SW and the precessional pico-second magnetization reversal. 11,12 As illustrated in Figs. 2͑b͒ and 2͑c͒, the SW strategy is to apply a large enough field to destroy the minimum initial state so that the particle can end up in the target state ͓Fig.…”
Section: Strategymentioning
confidence: 99%
“…This problem was first studied by Stoner and Wohlfarth 4 ͑SW͒ who showed that a field h larger than the SW-limit h SW can switch the magnetization from its initial state to the target value through a ringing effect. [5][6][7][8][9] However, recent theoretical and experimental studies [8][9][10][11][12] have shown that the minimal switching field can be smaller than the SW limit. Most studies have assumed the magnetic field to be time independent.…”
Section: Introductionmentioning
confidence: 99%
“…This generally involves starting a precession, stopping it, and keeping the magnetization stable along the desired new orientation. Coherent control and even precessional switching on the time scale of a few hundred picoseconds have been demonstrated by different methods based on the shaping of magnetic field pulses [3,7,8]. However, the limitations and complexity of these techniques have stimulated the search for alternative ways to create the equivalent of strong, ultrashort, and localized magnetic field pulses [9,10].…”
mentioning
confidence: 99%
“…This will stop the magnetization exactly in the reversed direction without any further oscillations, so-called ringing, that would otherwise slow down the overall reversal process. [6][7][8][9][10] Severals groups have studied the magnetization dynamics in thin patterned elements, 11,12 including the effects of defects and the resulting additional damping, 13 the localized precession modes that may exist in such elements, [14][15][16][17] and the approach for reducing the crosstalk between neighboring bits. 18,19 A particular problem is how to design an optimal field pulse to switch an element within half a precession period and then stopping the magnetization without any ringing.…”
mentioning
confidence: 99%